Programma: 9 september: Claw Boys Claw; 10 september: Mobid Angel, Grave Dismember; 12 september: Tower of Power; 13 september: Luka Bloom (1993)
Programma: 9 september: Claw Boys Claw; 10 september: Mobid Angel, Grave Dismember; 12 september: Tower of Power; 13 september: Luka Bloom.